The role of strategic leaders, big data analysis, and the investment decisions in building smart sustainable cities in the United Arab Emirates - Yousfi, Halah Muneer (2022)
The main challenges of this study are to show the prominent role of strategic leaders in analysing big data (BD) concerning investment decision-making (MID) capability to build an integrated smart city. In doing so, this study adopts and enriches the theory of networks, theories of situational administrative leadership and the theory of investment decision-making (MID). In particular, the theory of networks is utilised to emphasise the principle of digital government. Additionally, theories of situational administrative leadership and investment decision-making (MID) are adapted to examine the nexus of leadership practices and decision-making capacity. This study aims to examine the relationship between Strategic leadership (SL) practices, investment decision-making (MID), and big data (BD) analysis. This study is quantitative research based on a random sampling data collection method involving employees at the leadership level attached to the UAE's government departments. The sample size was 300 employees, with a 77% response rate. In total, 232 returned sample questionnaires were obtained, and where the hypotheses were verified. Based on multiplayer and hierarchical regression analyses, the research showed a significant and positive relationship between the dimensions of sustainable smart cities as a dependent variable on the one hand; and Strategic Leadership (SL), investment decision-making, and Big Data (BD) as independent variables on the other .Several logical reasons for the results that have some effective contributions to understanding these factors that can lead to building an integrated city supported by strategies that enable policy makers in the world to collect and exploit big data (BD) according to their priorities and accordingly, hypotheses were included and monitored, and presented. This study also presents recommendations for future research on developing an integrated smart city, strategic leadership, big data analysis and investment decision-making capacity.